This Is What Metabolic Dysfunction–Associated Steatotic Liver Disease Looks Like: Potential of a Multiparametric MRI Protocol - Fischer, Anja M.; Lechea, Nazim; Coxson, Harvey O. (Seminars in Liver Disease, 2024)
Metabolic dysfunction–associated steatotic liver disease (MASLD) is a prevalent condition with a broad spectrum defined by liver biopsy. This gold standard method evaluates three features: steatosis, activity (ballooning and lobular inflammation), and fibrosis, attributing them to certain grades or stages using a semiquantitative scoring system. However, liver biopsy is subject to numerous restrictions, creating an unmet need for a reliable and reproducible method for MASLD assessment, grading, and staging. Noninvasive imaging modalities, such as magnetic resonance imaging (MRI), offer the potential to assess quantitative liver parameters. This review aims to provide an overview of the available MRI techniques for the three criteria evaluated individually by liver histology. Here, we discuss the possibility of combining multiple MRI parameters to replace liver biopsy with a holistic, multiparametric MRI protocol. In conclusion, the development and implementation of such an approach could significantly improve the diagnosis and management of MASLD, reducing the need for invasive procedures and paving the way for more personalized treatment strategies.
Keywords: metabolic dysfunction–associated steatotic liver disease; magnetic resonance imaging; noninvasive tests; liver stiffness; hepatocyte function